Participatory Action Research on the Implementation of STEAM-Integrated Problem-Based Learning - Nurwati Djaman; Nur Wahidin Ashari; Irfan Pratama Amrin; Nabila Putri Amelia; Jabal Nur. D; Nur Inayah Anwar (Universitas Negeri Surabaya, 2026)
This study aimed to examine the implementation of a STEAM-based Problem-Based Learning (PBL) approach in mathematics learning to enhance students’ engagement, creativity, and problem-solving abilities. The research was conducted at SMP Negeri 26 Makassar using a Participatory Action Research (PAR) framework involving collaboration between university researchers, pre-service teachers, and the classroom teacher. The learning activities focused on the topic of arithmetic sequences and were designed following the stages of the PBL model integrated with STEAM elements (Science, Technology, Engineering, Arts, and Mathematics). Students worked collaboratively in small groups to analyze contextual problems, formulate hypotheses, conduct investigations using digital tools, and communicate their findings through digital presentations. Data were collected through classroom observations, learning artifacts, student presentations, and formative assessment results. Descriptive statistical analysis of the formative test scores showed that the average student score reached 92.5, with a median and mode of 90, indicating strong academic performance and relatively consistent achievement among students. The findings revealed that the STEAM-based PBL approach effectively promoted active participation, collaborative inquiry, and deeper conceptual understanding of arithmetic sequences. The integration of digital tools and interdisciplinary learning activities also supported the development of students’ critical thinking and communication skills. These results suggest that integrating STEAM within a PBL framework can provide meaningful and engaging mathematics learning experiences while improving students’ problem-solving abilities and overall learning outcomes.